Application Case Based Reasoning Method In Diagnosing Oil Palm Plant Diseases At PT Rapala, Gebang Sub-District - Hafizah Husna; Hotler Manurung; Arnes Sembiring (International Journal of Health Engineering and Technology, 2024)
In the last five years, the development of computers is very rapid. This can be seen from the number of computers owned by the community, with various sophistication and features and information systems that can spoil its users. One area of application that can be considered is the field of diagnosing oil palm plant diseases. Difficulties in diagnosing oil palm plant diseases at PT. RAPALA Kec. Gebang often occurs when you want to take preventive or curative action when an oil palm plant is attacked by a disease, because the old diagnostic system is due to limited experts so that the quality of operational performance is lacking. With the application of an expert system in diagnosing oil palm plant diseases, it is hoped that it will make it easier for field workers to diagnose oil palm plant diseases quickly without waiting for experts. This system is designed using PHP My Admin programming software and MySQL as database. The result of this study is the process of diagnosing diseases in oil palm plants using the Case Based Reasoning method where the design begins with entering symptom data, then the system calculates the diagnostic results according to the Case Based Reasoning method and displays it in the form of a report.